Comparative Study between Hydrodistillation and Microwave-assisted Hydrodistillation for Extraction of Cinnamomum Cassia Oil - Nitthiyah, Jeyaratnam; Nour, A. H.; Akindoyo, John Olabode (Asian Research Publishing Network (ARPN), 2016)
Microwave assisted hydrodistillation (MAHD) is an advanced technology extraction method that came up through the incorporation of microwave irradiation into the conventional method, hy drodiatillation (HD). In this research, both MAHD and HD methods have been compared and evaluated for their effective ness in the extraction of essential oil from (cinnamon) barks. The effect of various parameters such as microwave power level (200W, 225W, 250W and 275W), water to raw material ration (6:1, 8:1 and 10:1) and extraction time (30 mi n, 60 min, 90 min, 120 min, 150 min and 180 min) on the yield of extraction and its major constituents were investig ated and compared accordingly between MAHD and HD. At the optimum parameters of microwave power, 250W, water to ra w material ratio of 8:1 and extraction time of 90 min, the yield obtained was 2.55% and 1.89% for MAHD and HD respectively. Gas Chromatography/Mass Spectrometric (GC-MS) used to further analyse the effect of both extraction methods by evaluating the content of its main constituents which is trans-cinnamaldehyde and oxygenated compounds. Results rev ealed that MAHD method possesses highly desirable features than HD and could serve as an efficient and convenien t alternative to HD, especially in terms of its shorter extraction time, as well as the potentiality to produce reasonably good quantity and quality of cassia oil.